A tunable temperature-responsive and tough platform for controlled drug delivery. (6th July 2021) - Gao, Shuting; Zhou, Aying; Cao, Bin; Wang, Jing; Li, Fanghua; Tang, Guosheng; Jiang, Zhicheng; Yang, Anquan; Xiong, Ranhua; Lei, Jiandu; Huang, Chaobo
Abstract : A tunable temperature-responsive site-specific drug-delivery platform for tumor therapy. Abstract : Localized intelligent drug delivery systems (IDDSs) are promising platforms for solid tumor therapy with lower toxicity to physiological systems and improved curative effects due to efficiently controlled site-specific delivery of therapeutic molecules. To this end, a temperature-responsive tailorable fibrous localized drug-delivery system with enhanced mechanical properties to withstand the stress in vivo and temporal loading regimes for cancer treatment is developed. A series of PCM-functionalized PU–PCL core–shell fiber mats are prepared by coaxial electrospinning, which exhibit a tunable temperature response and controlled release capability. The in vitro release profiles observably show faster release of encapsulated molecules above 39 °C than that at lower temperatures under the same conditions and the study proves that the release conforms to biphasic release kinetics. The release profiles could be subtly regulated via tuning the mass fraction of the PCM. More importantly, the result of cytotoxicity assay shows the viability of cancer cells after treatment with hydroxycamptothecin (HCPT) release media at different temperatures and indicates that media containing HCPT released at 39 °C could kill significantly more cancer cells than those released below 39 °C, which confirms the temperature sensitivity of the prepared IDDSs. This work thus provides a promising intelligent platform for site-specific drug-delivery in solid tumor therapy.